Хроматографический метод контроля качества радиофармацевтического препарата; Известия вузов. Физика; Т. 55, № 11-2 - Большаков А. М. Алексей Михайлович; Гарапацкий А. А. Александр Александрович; Головков В. М. Владимир Михайлович; Семенов А. С. Алексей Сергеевич; Минин С. М. Станислав Михайлович (2012, 2012)
Заглавие с экрана